Design of a Modern Car Parking at the Faculty of Engineering, Technology Applied Design and Fine Art. (Kabale University, 2023)
To find a feasible solution to the problem statement we went through various steps to get them accomplished. Chapter one entails the introduction to the project, the background, the problem statement, justification of the problem, specific objective, main objectives among others. Chapter two explains the various methods employed to come out with the design like bench marking, data collection, designing among others. Chapter three gives explanation or the various sources of our analysis, study and research.